Bioassay screening of 12 Iranian plants and detection of antibacterial compounds from Heracleum persicum using a TLC bioautography method. Issue 11 (20th July 2020) - Dehghan, Hossein; Rezaee, Parizad; Aliahmadi, Atousa
Abstract: Allium paradoxum, Buxus hyrcana, Convolvulus persicus, Cyclamen coum, Eryngium caucasicum, Heracleum persicum, Pimpinella affinis, Parrotia persica, Primula heterochroma, Pyrus boissieriana, Ruscus hyrcanus, and Smilax excelsa are some medicinal and food flavoring plants found in the Hyrcanian forests in Iran. This study was designed to determine the most potent antibacterial compounds from the plants. The MIC values of n -hexane, ethyl acetate, and methanol extracts of different parts of the plants (63 extracts) were determined against Staphylococcus aureus, B. cereus, Pseudomonas aeruginosa, and Salmonella entritidis . The antibacterial compounds of the most potent extracts were determined by TLC bioautography, against S. aureus . According to the results, the n -hexane extract of the roots of H. persicum was selected to identify its bioactive phytochemicals. In the following, eight furanocoumarins, heratomin, xanthotoxin, isobergapten, bergapten, pimpinellin, isopimpinellin, moellendorffilin, and sphondin were identified by comparing with purified standards in different solvent systems. Among these compounds, moellendorffilin played a dominant role and exhibited significant activities against S. aureus, B. cereus, P. aeruginosa, and S. entritidis, with MIC values 31.25, 31.25, 62.5, and 15.62 µg/mL, respectively. Accordingly, H. persicum could be regarded as a promising high-potential plant and inexpensive source of antibacterial compounds for the pharmaceutical and food industries. Graphical Abstract: